Pipelined architectures for the frequency domain linear equalizer - Glentis, George-Othon; Georgoulakis, Kristina (Zielona Góra: Uniwersytet Zielonogórski)
In this paper, novel pipelined architectures for the implementation of the frequency domain linear equalizer are presented. The Frequency Domain (FD) LMS algorithm is utilized for the adaptation of equalizer coefficients. The pipelining of the FD LMS linear equalizer is achieved by introducing an amount of time delay into the original adaptive scheme, and following proper delay retiming.
Keywords: adaptive equalization; frequency domain LMS; pipelined implementation